ON SOME CONCEPTS RESPECT TO WEAK STRUCTURES - Shaloof, Aml Melad; Hamid, Halima Ali (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
In this paper, we use the concept of a weak structure to introduce some new concepts such as sub weak structure, separation, connectedness and sub connected space. Furthermore, investigate some theorems with their proofs and state examples.